Simultaneous Shape and Size Optimization of Double-layer Grids with Nonlinear Behavior - Kaveh, Ali; Moradveisi, Mehran (Periodica Polytechnica Civil Engineering, 2020)
The main aim of this paper is to present a new solution for simultaneous shape and size optimization of double-layer grids. In order to find the optimum design, Enhanced Colliding Bodies Optimization method is applied to the optimum design of the most common examples of double-layer grids, while both material and geometrical nonlinearity are taken into account. The small and big sizes of span length are considered for each type of square grids. The algorithm gets the minimum weight grid by finding the best nodal location in z-direction (height of the structure) and the suitable selection from the list of tube sections available in American Institute of Steel Construction Load and Resistance Factor Design, simultaneously. All examples are optimized with strength and displacement constraints. The numerical results demonstrate the efficiency and robustness of the presented method for solving real-world practical double-layer grids.